Geometry Textbook Development Based on Gorontalo Local Wisdom for Elementary School Students - Huljannah, Miftha; Yahiji, Kasim; Anwar, Herson (Journal of Elementary Educational Research, 2024)
The current use of geometry textbooks in elementary schools still focuses on abstract theories and concepts, adhering to national standards that do not always align with local cultural characteristics. The development of a geometry teaching material based on the local wisdom of Gorontalo was chosen as one of the solutions to this issue. This research and development utilized the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects of the study were fourth, fifth, and sixth-grade students and teachers at MIT Al-Ishlah and SDN 3 Bulango Ulu. Data were collected through evaluation tests, expert validation questionnaires, and questionnaires for teachers and students. The results of the validation by content experts, language experts, and media experts were 78.4%, 83.33%, and 94.64%, respectively, all categorized as "valid." The responses from teachers and students during the trial phase were 83.33% and 81.71%, respectively, both categorized as "very practical." Thus, the Geometry Textbook Based on Local Wisdom of Gorontalo: Plane Figures and Solid Figures for 4th, 5th, and 6th Grade Students can be declared valid and practical for use in teaching.